2023
DOI: 10.1051/0004-6361/202244309
|View full text |Cite
|
Sign up to set email alerts
|

How much metal did the first stars provide to the ultra-faint dwarfs?

Abstract: Numerical simulations of dwarf galaxies have so far failed to reproduce the observed metallicity-luminosity relation, down to the regime of ultra-faint dwarfs (UFDs). We address this issue by exploring how the first generations of metal-free stars (Pop III) could help increase the mean metallicity ([Fe/H]) of those small and faint galaxies. We ran zoom-in chemo-dynamical simulations of 19 halos extracted from a Λ Cold Dark Matter (CDM) cosmological box and followed their evolution down to redshift z = 0. Model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 144 publications
2
17
0
Order By: Relevance
“…In the right panel of Figure 12, we compare the dwarf galaxy data against simulated UFDs from the independent simulations of Jeon et al (2017), Wheeler et al (2019), Agertz et al (2020), andSanati et al (2023). While simulations have begun to reproduce the mean metallicities of UFDs more luminous than 10 4 L e , fainter UFDs still remain a theoretical challenge to simulate.…”
Section: Faint End Of the Dwarf Galaxy Mass-metallicity Relationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the right panel of Figure 12, we compare the dwarf galaxy data against simulated UFDs from the independent simulations of Jeon et al (2017), Wheeler et al (2019), Agertz et al (2020), andSanati et al (2023). While simulations have begun to reproduce the mean metallicities of UFDs more luminous than 10 4 L e , fainter UFDs still remain a theoretical challenge to simulate.…”
Section: Faint End Of the Dwarf Galaxy Mass-metallicity Relationmentioning
confidence: 99%
“…In the case of FIRE-2 simulations, which implement strong feedback, many of the lowest-luminosity UFDs never enrich beyond the initialized metallicity floor (Wheeler et al 2019), as shown by the lowerluminosity FIRE UFDs in Figure 12 at [Fe/H]= −4.0. So far, there have been numerical experiments varying parameters such as star formation, radiative transfer, SNe energies (Agertz et al 2020;Sanati et al 2023), metallicity-dependence of Type Ia SNe DTDs (Gandhi et al 2022), and top heaviness and stochastic sampling of the IMF (Applebaum et al 2020;Prgomet et al 2022 respectively), in order to explore the parameter space of physics that elevate enrichment levels in UFDs. Overall, this area of study is still ongoing.…”
Section: Faint End Of the Dwarf Galaxy Mass-metallicity Relationmentioning
confidence: 99%
“…In the future, we plan on including the formation of Pop III stars in the simulation, as carried out in a recent study by Sanati et al (2023) with the smoothed-particle hydrodynamics(SPH) code GEAR. It will be interesting to see if this result is influenced by pure Pop III star formation since Pop III stars are expected to survive in pristine clumps down to redshift z = 6 (Liu & Bromm 2020).…”
Section: Summary Discussion and Conclusionmentioning
confidence: 99%
“…Ultrafaint dwarf galaxies (UFDs), which are known as the smallest unit of galaxies with the lowest luminosity (L < 10 5 L ☉ ) and stellar mass (10 2 M e < M * < 10 5 M e ) in the Universe, have been considered as the fundamental building blocks of massive galaxies (reviewed in Simon 2019; see also Tolstoy et al 2009;McConnachie 2012). Additionally, due to their shallow potential wells, UFD systems are highly vulnerable to internal and external feedback effects, making them an excellent laboratory for studying how feedback mechanisms change star formation activities in small systems (e.g., Stinson et al 2007;Sawala et al 2010;Simpson et al 2013;Agertz & Kravtsov 2015;Jeon et al 2017;Wheeler et al 2019;Agertz et al 2020;Rey et al 2020;Gutcke et al 2022;Sanati et al 2023).…”
Section: Introductionmentioning
confidence: 99%